THE INFLUENCE OF EDUCATION LEVEL TO COASTAL AND WATERSHED ZONE OF OPAK RIVER - Trisno Fallo; Jovita Irene Pongoh; Febriyanti Angelia Ginting (Universitas Medan Area, 2018)
Education level contributes to community’s mindset and knowledge in terms of environmental conservation management and awareness. Coastal and watershed zone management of Opak River, Bantul district, is measured based on education level. Coastal and watershed zone management should consider environmental aspects of the watershed region. Watershed zone conservation is determined by community’s mindset, behavior, and awareness. The objectives of this study are (1) to identify the influence of education level to coastal and watershed zone management in Kretek Sub-district, Bantul District. (2) to identify current coastal and watershed zone management in Kretek Sub-district, Bantul District. This study uses a descriptive method using literature study from relevant information sources collected from various literatures. Data collection techniques used in this study are observations, questionnaires, and interviews. Study results show no influence of education level to coastal and watershed zone management of Opak River.